2019
DOI: 10.1088/1674-4527/19/9/136
|View full text |Cite
|
Sign up to set email alerts
|

Triple Range Imager and POLarimeter (TRIPOL)—a compact and economical optical imaging polarimeter for small telescopes

Abstract: We report the design concept and performance of a compact, light-weight, and economic imaging polarimeter, TRIPOL (the Triple Range Imager and POLarimeter), capable of simultaneous optical imagery and polarimetry. TRIPOL splits the beam from wavelength 400 to 830 nm into g ′ -, r ′ -, and i ′ -bands with two dichroic mirrors, and measures polarization with an achromatic half-waveplate and a wire-grid. The simultaneity makes TRIPOL a useful tool for small telescopes for photometry and polarimetry of time variab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Polarimetric data of HO Pup were well obtained in r and i bands (but it were too faint in the g band), as reported in Table 3. We have also observed a number of unpolarized and polarized standard stars (Schmidt et al 1992) to calibrate the instrumental polarization and angle offset (Sato et al 2019). Based on the observations of these standard stars, we found that the performance of TRIPOL2 was very stable during those nights for both the measurements of polarization percentages (using both polarized and unpolarized standard stars) and the polarization position angles (using the unpolarized standard stars); for more details, see Huang (2019).…”
Section: Polarimetric Datamentioning
confidence: 96%
See 1 more Smart Citation
“…Polarimetric data of HO Pup were well obtained in r and i bands (but it were too faint in the g band), as reported in Table 3. We have also observed a number of unpolarized and polarized standard stars (Schmidt et al 1992) to calibrate the instrumental polarization and angle offset (Sato et al 2019). Based on the observations of these standard stars, we found that the performance of TRIPOL2 was very stable during those nights for both the measurements of polarization percentages (using both polarized and unpolarized standard stars) and the polarization position angles (using the unpolarized standard stars); for more details, see Huang (2019).…”
Section: Polarimetric Datamentioning
confidence: 96%
“…In addition to the photometric and spectroscopic observations, we also took polarimetric data by using the TRIPOL2 (second generation of the Triple Range Imager and Polarimeter) instrument (Sato et al 2019), equipped on the Lulin One-meter Telescope (LOT), in 2018 October. TRIPOL2 can simultaneously take polarization images in Sloan g′, r′, and i′ bands with the half-wave plate rotating to four angles: 0°, 22°.5, 45°, and 67°.5.…”
Section: Polarimetric Datamentioning
confidence: 99%